2000
DOI: 10.1021/ja993306i
|View full text |Cite
|
Sign up to set email alerts
|

Topochemical Synthesis of Three-Dimensional Perovskites from Lamellar Precursors

Abstract: A topochemical route to nondefect, three-dimensional perovskites from lamellar Dion-Jacobson and Ruddlesden-Popper precursors was demonstrated. The method involves reduction of one of the ions (in this case Eu 3+ ) in the precursor phase and concomitant loss of oxygen. CsEu 2 Ti 2 NbO 10 , a three-layer Dion-Jacobson compound, was ion-exchanged to AEu 2 Ti 2 NbO 10 (A ) Na, Li) and reduced in hydrogen to form the SrTiO 3 -type perovskites AEu 2 Ti 2 NbO 9 . Similarly, K 2 Eu 2 Ti 3 O 10 , a three-layer Ruddles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 51 publications
2
92
0
Order By: Relevance
“…Typical examples are the conversion of the layered perovskite to perovskite (Schaak & Mallouk, 2000) and the preservation of the packing direction of closed-packed layers. (Zeng et al, 2006).…”
Section: Different Structures Between Precursors and Productsmentioning
confidence: 99%
“…Typical examples are the conversion of the layered perovskite to perovskite (Schaak & Mallouk, 2000) and the preservation of the packing direction of closed-packed layers. (Zeng et al, 2006).…”
Section: Different Structures Between Precursors and Productsmentioning
confidence: 99%
“…In addition, Aurivillius and R-P phases could be interchanged by the selective leaching of Bi O sheet and metathesis reaction (7,8). Schaak and Mallouk have prepared an A-site ordered 3-D perovskite, CaEu Ti O , from n"3 R-P phase Na Eu Ti O (9). Very recently, we have demonstrated that the B-site cations in Cs¸n Ti NbO (¸n"La, Pr, Nd, Sm) are arranged into the new-type ordering sequence of (Ti Nb )O }TiO }(Ti Nb )O (10).…”
mentioning
confidence: 99%
“…[42] The raw materials SrCO 3 , Ta 2 O 5 , and K 2 CO 3 (40 mol-% excess) were thoroughly mixed and calcined at 850°C for 6 h and sintered at 1200°C for 10 h. Ion exchange [43][44][45] (Figure 1a), which was used for synthesizing metastable Sr 0.5 TaO 3 with a threedimensional perovskite structure (Figure 1d). Sr 0.5 TaO 3 powder was prepared by two different processes: (1) direct dehydration of the host material [44,[46][47][48][49][50] and (2) nanosheet processing (Figure 1). In the direct dehydration process, the host material H 2 Sr 1.5 Ta 3 O 10 was dehydrated by heat treatment at 600°C for 2 h in air, which led to Sr 0.5 TaO 3 powder.…”
Section: Methodsmentioning
confidence: 99%